Comparative Effects of Teriparatide, Denosumab, and Combination Therapy on Peripheral Compartmental Bone Density, Microarchitecture, and Estimated Strength: the DATA‐HRpQCT Study. (January 2015) - Tsai, Joy N; Uihlein, Alexander V; Burnett‐Bowie, Sherri‐Ann M; Neer, Robert M; Zhu, Yuli; Derrico, Nicholas; Lee, Hang; Bouxsein, Mary L; Leder, Benjamin Z
ABSTRACT Combined teriparatide and denosumab increases spine and hip bone mineral density more than either drug alone. The effect of this combination on skeletal microstructure and microarchitecture, however, is unknown. Because skeletal microstructure and microarchitecture are important components of skeletal integrity, we performed high‐resolution peripheral quantitative computed tomography (HR‐pQCT) assessments at the distal tibia and radius in postmenopausal osteoporotic women randomized to receive teriparatide 20 µg daily (n = 31), denosumab 60 mg every 6 months (n = 33), or both (n = 30) for 12 months. In the teriparatide group, total volumetric bone mineral density (vBMD) did not change at either anatomic site but increased in both other groups at both sites. The increase in vBMD at the tibia was greater in the combination group (3.1 ± 2.2%) than both the denosumab (2.2 ± 1.9%) and teriparatide groups (–0.3 ± 1.9%) (p < 0.02 for both comparisons). Cortical vBMD decreased by 1.6 ± 1.9% at the tibia and by 0.9 ± 2.8% at the radius in the teriparatide group, whereas it increased in both other groups at both sites. Tibia cortical vBMD increased more in the combination group (1.5 ± 1.5%) than both monotherapy groups (p < 0.04 for both comparisons). Cortical thickness did not change in the teriparatide group but increased in both other groups. The increase in cortical thickness at the tibia was greater in the combination group (5.4 ± 3.9%) than both monotherapy groups (p < 0.01 for both comparisons). In the teriparatide group, radial cortical porosity increased by 20.9 ± 37.6% and by 5.6 ± 9.9% at the tibia but did not change in the other two groups. Bone stiffness and failure load, as estimated by finite element analysis, did not change in the teriparatide group but increased in the other two groups at both sites. Together, these findings suggest that the use of denosumab and teriparatide in combination improves HR‐pQCT measures of bone quality more than either drug alone and may be of significant clinical benefit in the treatment of postmenopausal osteoporosis. © 2014 American Society for Bone and Mineral Research.